2015
DOI: 10.18203/issn.2454-5929.ijohns20150900
|View full text |Cite
|
Sign up to set email alerts
|

Granular myringitis: current status of management

Abstract: <p class="abstract"><span lang="EN-US">The Granular Myringitis (GM) is not uncommon though in medical literature it has been reported among the rarer conditions. The aim of this article is to review the clinical features and management of Granular Myringitis (GM). GM is characterized by granulation tissue on the outer surface of the Tympanic Membrane (TM) with or without the involvement of deep bony External Auditory Canal (EAC). The granulations are either localized or diffuse. The granulations ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Chronic myringitis was stated to induce tympanic membrane perforation . However, evidence for this appears to be lacking, and the mechanism of the perforation of the tympanic membrane observed in myringitis is also uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic myringitis was stated to induce tympanic membrane perforation . However, evidence for this appears to be lacking, and the mechanism of the perforation of the tympanic membrane observed in myringitis is also uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic myringitis was stated to induce tympanic membrane perforation. 25 However, evidence for this appears to be lacking, and the mechanism of the perforation of the tympanic membrane observed in myringitis is also uncertain. Myringitis tends to show very unconverted features regardless of the type (e.g., granulomatous or ulcerative).…”
Section: Mechanisms Of Myringitismentioning
confidence: 99%
“…The author has observed that once the patients give up the habit of self cleaning of ear and resist the desire of scratching EAC the number and frequency of their visits reduce significantly and they recover fully with conservative medical treatment (meticulous microscopic aural toilet and topical antibiotic and steroid ear drops). Only few patients needed application of topical caustic agents (such as chromic acid, formalin, or silver nitrate) or surgical excision of granulation tissue and reconstructive ear-microsurgery [23].…”
Section: Discussionmentioning
confidence: 99%
“…2 Various modalities of treatment have been employed in the management of this disorder. 3 GM is not rare 4 and has various types of lesions, which vary in extension and can have important bearing on the line of treatment and prognosis. It can affect not only TM but can also extend to deep bony external auditory canal (EAC).…”
Section: Introductionmentioning
confidence: 99%
“…4,7,8 Medical and surgical intervention is varied and often does not lead to permanent resolution of the disease. 3,9 Untreated GM can lead to inflammatory infiltration of the deep EAC and post-inflammatory medial EAC fibrosis and its atresia. 10 In spite of all these varied otoscopy findings, sequelae (causing hearing impairment), and diverse treatments, currently there is no classification and staging system of GM.…”
Section: Introductionmentioning
confidence: 99%